A Methodology for Searching and Allocating Enterprises in the Supply Chain by Using the Business Information Database and Trademark Rights Database. (November 2017) - Lim, Daehyeon; Moon, Youngsu; Kim, Kanghoe; Lee, Hoshin
As a number of support programmes for competence improvement are provided to small and medium enterprises (SMEs) in Korea, it is recommended that these enterprises collaborate with each other. However, without information about other enterprises in the industry that they belong to or are planning to enter, many SMEs f ind it diff icult to look for partners that they can collaborate with. This article focuses on extracting a list of enterprises in a supply chain of a specif ic industry through a business information database and a Korean trademark rights database. Also, it focuses on suggesting a methodology that would show a list of actual deals made between enterprises found through a business deal database. Through these, it becomes possible for SMEs to have knowledge about other enterprises and their previous deals in a supply chain or a system of a specif ic industry. SMEs will thus be able to build a suitable business plan based on such information. Moreover, this article will be helpful for policymakers as it will help them understand the system and characteristics of the industry and come up with a suitable programme for the industry that can support SMEs.